Chaos in Quantum Mechanics - Rahman, Md. Mahfujur; Pandey, Sovers Tonmoy (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.